Dopaminergic Suppression of Synaptic Transmission in the Lateral Entorhinal Cortex - Caruana, Douglas A. (Hindawi Publishing Corporation, 2008)
Dopaminergic projections to the superficial layers of the lateral entorhinal cortex can modulate the strength of olfactory inputs to the region. We have found that low concentrations of dopamine facilitate field EPSPs in the entorhinal cortex, and that higher concentrations of dopamine suppress synaptic responses. Here, we have used whole-cell current clamp recordings from layer II neurons to determine the mechanisms of the suppression. Dopamine (10 to 50 μM) hyperpolarized membrane potential and reversibly suppressed the amplitude of EPSPs evoked by layer I stimulation. Both AMPA- and NMDA-mediated components were suppressed, and paired-pulse facilitation was also enhanced indicating that the suppression is mediated largely by reduced glutamate release. Blockade of D(2)-like receptors greatly reduced the suppression of EPSPs. Dopamine also lowered input resistance, and reduced the number of action potentials evoked by depolarizing current steps. The drop in input resistance was mediated by activation of D(1)-like receptors, and was prevented by blocking K(+) channels with TEA. The dopaminergic suppression of synaptic transmission is therefore mediated by a D(2) receptor-dependent reduction in transmitter release, and a D(1) receptor-dependent increase in a K(+) conductance. This suppression of EPSPs may dampen the strength of sensory inputs during periods of elevated mesocortical dopamine activity.